2018
DOI: 10.1371/journal.pone.0201010
|View full text |Cite
|
Sign up to set email alerts
|

Internal limiting membrane peeling versus no peeling during primary vitrectomy for rhegmatogenous retinal detachment: A systematic review and meta-analysis

Abstract: BackgroundInternal limiting membrane (ILM) peeling during primary vitrectomy for rhegmatogenous retinal detachment (RRD) prevents the formation of postoperative macular epiretinal membrane (ERM). However, studies that compared vitrectomy with and without ILM peeling for RRD, have reported controversial outcomes.ObjectiveTo assess the efficacy of ILM peeling versus non-ILM peeling during vitrectomy for RRD by a systematic review and meta-analysis of published studies.MethodsPubMed, Medline, Web of Science, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 29 publications
(71 reference statements)
0
44
0
Order By: Relevance
“…All these support a good quality level of evidence. Moreover, a meta-analysis has more accurate confidence and higher power than a single report 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…All these support a good quality level of evidence. Moreover, a meta-analysis has more accurate confidence and higher power than a single report 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…using the Newcastle–Ottawa Quality Assessment Scale (NOS), which evaluates patient selection, comparability of degenerative LMH group and tractional LMH group, and outcome [ 14 ]. The risk of bias for each included study was categorized as high when the NOS score was < 6, and low-to-moderate when ≥6 [ 15 ]. Publication bias was evaluated by examination of the funnel plot for evidence of asymmetry and the Egger regression test.…”
Section: Methodsmentioning
confidence: 99%
“…We also excluded eyes with fovea-sparing RRDs to avoid any potential complications of performing ILM peeling on a non-diseased macula. A recent meta-analysis of studies comparing ILM peeling versus no peeling during PPV for RRD found the incidence of postoperative macular ERM formation to be significantly lower in patients who had ILM peeling, but this bared no significant effect on postoperative visual outcomes [3].…”
Section: Discussionmentioning
confidence: 99%
“…ERMs may develop after successful vitrectomy for repair of rhegmatogenous retinal detachment (RRD) with an incidence that varies from 6 to 48% according to published literature [3]. Risk factors for post-PPV ERM development include multiple, large or posterior retinal breaks, as well as a longer duration of macular detachment [4,5].…”
Section: Introductionmentioning
confidence: 99%